ANALYSIS OF THE EFFECTIVENESS OF TAX INCENTIVES ON THE TAX COMPLIANCE BEFORE AND DURING THE COVID-19 PANDEMIC (STUDY ON MSME DIGITAL AND MSME NON-DIGITAL) - Muhamad Safiq; Sherlyne Balqist Setyo Afrilin (Jurnal Cakrawala Ilmiah, 2022)
The purpose of this research is to evaluate how the provision of tax incentives PMK No. 82/PMK.03/2021, tax socialization, and tax administration affect tax compliance in the COVID-19 pandemic situation, as well as to determine whether the taxpayer's perspective moderates the relationship between PMK tax incentives No. 82/PMK.03/2021, tax socialization, tax administrative services, and tax sanction on taxpayer compliance. This research utilizes both qualitative and quantitative analysis, as well as secondary and primary data. The number of respondents in this study was composed of 5 respondents who participated in the Focus Group Discussion (FGD) and 258 respondents from the questionnaire data. Non-probability sampling, often known as purposeful sample, was used in this study. The Sequential Equation Model-Partial Least Squares (SEM-PLS) was used to collect data through interviews and web-based surveys. Tax incentives PMK No.82/PMK.03/2021, tax socialization, and tax administrative services all had a positive effect on taxpayer compliance, according to the findings. This demonstrates that the implementation of tax policies based on the Covid-19 condition has the potential to influence taxpayer compliance especially MSMEs in the city and district of Blitar, despite their diverse business backgrounds, knowledge, and ages. Furthermore, in the COVID-19 pandemic, taxpayer perception can influence the relationship between tax incentives PMK No. 82/PMK.03/2021 and tax administrative on taxpayer compliance. In contrast to tax administration, where taxpayer perception cannot moderate its relationship with taxpayer compliance